Re-Connecting with a Historical Site: On Narrative and the Huron-Wendat Ancestral Village at York University, Toronto, Canada - Sandberg, L. Anders; Johnson, Jon; Gualtieri, Rene; Lesage, Louis (Ontario History)

(untitled) (The Ontario Historical Society, 2021)
The ‘Parsons site,’ a large Huron-Wendat village site near York University’s Keele campus located by archaeologists in the early 1950s, has been subject to a variety of investigations and development proposals which have mobilized certain narratives about the site and its inhabitants. This article provides an analysis of how these narratives represent the site, its inhabitants, and contemporary Huron-Wendat. It problematizes narratives that describe the site as an archaeological resource and situate Huron-Wendat presence in the past. Although these narratives have shifted to acknowledge ongoing Huron-Wendat presence, more collaboration with contemporary Huron-Wendat communities regarding this and other sites is needed.